The Blackwell Companion to the Qur’an: By Andrew Rippin, ed. Malden, (Massachusetts: Blackwell Publishing, 2006. 576 pages.) (American Journal of Islam and Society, 2009)
With The Blackwell Companion to the Qur’an,Andrew Rippin, an illustriousscholar in the field of Qur’anic studies, presents yet another impressivecontribution to previous collections of articles on the Qur’an that he hasedited: Approaches to the History of the Interpretation of the Qur’an (OxfordUniversity Press: 1988); The Qur’an: Formative Interpretations (Variorum: 1999); and, with Khaleel Mohammed, Coming to Terms with the Qur’an: AVolume in Honor of Issa Boullata (Islamic Publications International: 2008),just to name a few. Gathering the works of scholars from leading universitiesthroughout the world, Rippin has constructed a volume that is designednot only for the general reader “who may have little exposure to the Qur’anbeyond a curiosity evoked by the popular media” (p. x), but also to scholarsspecializing in the Qur’an. The overall aim of this large volume, which comprisesthirty-two articles, is to guide the reader to “a well-advanced state ofunderstanding the complexities of the text and its associated traditions”(ibid) ...